(untitled) (Bangladesh Agronomy Journal, 2023)
A pot experiment was conducted during 2018-19 in a net house at the Department of Soil Science, Sher-e-Bangla Agricultural University, Dhaka, to determine fertilizer’s effect on the growth and yield of Boro and T. Aman rice in the soils of industrially polluted agricultural land areas of Madhupur Tract. The study consisted of two factors, i.e., polluted soil viz., S1: Non-polluted soil, S2: polluted soil-1, S3: polluted soil-2, S4: polluted soil-3, and four fertilizer treatments viz., T0: Control, T1: N150P30K60S20Zn3.0 (100%RDCF), T2: N105P21K42S14Zn2.1 (70%RDCF) T3: N75P15K30S10Zn1.5(50%RDCF) The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Among the soils, the highest Boro rice grain yield of 90.83 g pot-1 was found in S2 (polluted soil-1) soil, and the lowest 41.66 g pot-1 in soil S1 (Non-polluted soil). The treatment T3(50% RDCF) fertilizer treatment gave the highest plant height (84.12 cm), effective tillers (42.5 hill–1), straw (112.58g pot –1) and grain yield (80.03g pot−1) of Boro rice. The higher grain and straw yields of Boro rice were obtained from two industrially polluted soils (S2 and S4). The maximum grain yield (112.3g pot–1) of Boro was found in S2T3 (Contaminated soil 1 and 50% RDCF) , which was statistically similar to S4T2 and S4T3 and lowest in the S1T0 treatment combination. The maximum T. Aman grain yield (38.75gpot−1) was obtained in soil S2 (polluted soil-1), which at par to S4 (polluted soil-3). The maximum T. Aman rice grain yield (36.68 g pot−1) was found in the T2 treatment, which was closely by T1 treatment. Similarly, the maximum T. Aman grain yield was obtained in S2T1 (Contaminated soil 1 and 100% RDCF) which was statistically similar to S2T2, S4T1, and S4T2 and lowest in the S1T0 treatment combination. The highest T. Aman straw yield was found in the S3T1 and lowest in the S1T0 treatment combination. Bangladesh Agron. J. 2023, 26(1): 112-121